On Chaos in the Fractional-Order Discrete-Time Unified System and Its Control Synchronization - Amina-Aicha Khennaoui; Adel Ouannas; Samir Bendoukha; Xiong Wang; Viet-Thanh Pham (Entropy, 2018)
In this paper, we propose a fractional map based on the integer-order unified map. The chaotic behavior of the proposed map is analyzed by means of bifurcations plots, and experimental bounds are placed on the parameters and fractional order. Different control laws are proposed to force the states to zero asymptotically and to achieve the complete synchronization of a pair of fractional unified maps with identical or nonidentical parameters. Numerical results are used throughout the paper to illustrate the findings.